Skrining fitokimia dan isolasi senyawa flavonoid dari ekstrak etanol kulit buah menteng (Baccaurea racemosa (Reinw.) Müll.Arg) - Muhammad Ari Mukhtizar; Haris Munandar Nasution; M. Pandapotan Nasution; Rafita Yuniarti (Journal of Pharmaceutical and Sciences, 2023)
The menteng plant, which belongs to the Euphorbiaceae family, is a subtropical plant worldwide. Flavonoids are one of the groups of phenolic compounds found in plant tissues that can act as antioxidants. This research aimed to determine the class of chemical compounds found in the Menteng fruit peel and determine the characteristics of fruit peel flavonoids by UV Spectrophotometry and IR Spectrophotometry. %. Phytochemical screening showed positive for alkaloids, flavonoids, and steroids/triterpenoids, while tannins, saponins, and glycosides were negative from 400 grams of simplisia produced 39.1 grams of viscous extract. Characterization of crystal isolates of UV spectrophotometry showed a wavelength of 280 nm, inferred to be a flavanoid. The results of IR spectrophotometry show the O-H, C-H aliphatic, C=C aromatic, C=O, C-H, and C-O groups.